Gravity Centers of Central European Urban Network – Global Embeddedness Based on Advanced Producer Services - Katalin Döbrönte (DETUROPE)
The focus of the paper is on how Central-European cities can join the global urban network by taking part in offering high level business services for multinational companies. Companies offering these high level business services are multinational companies themselves, which locate their offices in the production and service-providing centers. New centralities and marginalities occur, and a key question how the fragmented Central European urban structure mainly characterised by small cities is affected by these changes, which cities became global cities, and which cities can be integrated in the urban network on a regional level. The hypothesis is justified by the examinations, mainly the integration of capital cities can be witnessed. Primary gravity centers are Warsaw and Vienna, besides Prague and Budapest can be identified as global cities of the region. The Central-European space is connected as a macro-region, all capital cities are on the map of examination, no new periphery occurs on macro level. The role of big cities apart from capital cities is in strong correlation with the relevant country’s urban network, with its mono- vs polycentric type of organization.